Lingvostilističeskij aspekt interpretacii ègocentričeskihtekstovyh struktur - Gončarova, Evgeniâ A. (Stylistyka, 2021)
The article presents a comparative scientific description of anthropocentrism and egocentrism which are regarded as factors in text formation, their logical relation being that of “general" and “particular”. The concept of “egocentric text" is introduced and those linguostylistic units whose hierarchical interaction determines the structural, semantic and pragmatic features of the egocentric text in different spheres of communication are analysed in the article.